Impact of Cryptocurrency Market Fluctuations on Traditional Stock Market Volatility in Japan - Yamamoto , Aiko (International Journal of Finance, 2025)
Purpose: The purpose of this article was to analyze impact of cryptocurrency market fluctuations on traditional stock market volatility in Japan. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study on the impact of cryptocurrency market fluctuations on traditional stock market volatility in Japan found a significant correlation between the two markets. It concluded that cryptocurrency price movements often act as a leading indicator of stock market volatility, with large swings in cryptocurrency values tending to precede similar volatility in the stock market. The study suggested that while cryptocurrencies and traditional stocks are distinct markets, increased investor participation in cryptocurrencies has led to greater interdependence. This relationship is particularly evident during periods of market uncertainty, where both markets show heightened volatility. Unique Contribution to Theory, Practice and Policy: Efficient market hypothesis (EMH), contagion theory & behavioral finance theory may be used to anchor future studies on the impact of cryptocurrency market fluctuations on traditional stock market volatility in Japan. Providing financial literacy programs alongside these products will empower underserved communities to participate more fully in the economy. Policymakers in Brazil should adopt a coordinated approach to financial inclusion, involving the central bank, financial institutions, and technology companies.